Student and Staff Perspectives on Important Employability and Global Mobility Skills for Health Professionals in Higher Education - Karan, R. Chadda; Jennifer, Routh; Tizreena, Ismail; Sasikala Dev, Amirthalingam; Chaisiri, Angkurawaranon; Viroj, Boonyaratanakornkit; Dayang Zuraina, Abang Haji Kassim; Dayangku Norlida, Awang Ojep; Sabrina, Lukas; Asri, Said; Kamalan, Jeevaratnam (Wiley-Blackwell, 2026)
This study investigated what value health professional students and staff place on employability and global mobility training. It investigated the most important employability and global mobility characteristics, and how perceptions vary between students and academics. The study used an anonymous, online questionnaire distributed to health professional students and academic staff at the University of Surrey (UK) and the University of Malaysia, Sarawak (Malaysia). The outcomes of pairwise comparison questions were processed using the Elo algorithm to generate importance rankings of the employability and global mobility characteristics. One hundred and forty-two students and 42 academics were included. The most important employability and global mobility characteristics were an ability to get along with people from different cultural backgrounds, adaptability, openness to new experiences, an ability to read situations and respond to them, communication skills, and problem-solving. The characteristics that were ranked highly by academics were also likely to have high rankings by students. This study demonstrates that students and academics value employability and global mobility teaching and give similar ratings to specific characteristics. The next stepis to investigate how these characteristics can be incorporated into higher education curricula and adapted over time in response to evolving workforce requirements.